On the nature and role of the lower crust in the volcanic front of the Trans-Mexican Volcanic Belt and its fore-arc region, southern and central Mexico - Fernando Ortega-Gutiérrez; Mariano Elías-Herrera; María Guadalupe Dávalos-Elizondo (Revista Mexicana de Ciencias Geológicas)
With the main objective of further constraining models that debate how and where magmas are generated in the Mexican subduction factory, how they ascend through the overlying viscous layers, and how and where they interact with the traversed crust to produce the diversity of the magmas that compose the system, the nature of the lower crust and its immediate surroundings under the volcanic front of the Trans-Mexican Volcanic Belt (TMVB), as well as its fore-arc in southern Mexico, are analyzed and integrally characterized in this work. The study is mainly based on the analysis of geophysical and geological existing and new data, as well as on our new data obtained from deep-seated xenoliths. Taken as that part of the crust located from the Moho to a depth of 20–25 km below the surface, it is concluded from our analysis that all of the lower crust in the study area should be in the granulite facies, if geophysical modeling correctly predicted temperatures of 700–800ºC for its base, and a crustal thickness varying between 40 and 45 km. Xenoliths and surface geology information, when integrated to tectonic modeling, support the notion that most of the lower crust under the eastern and central sectors of the TMVB should be of Mesoproterozoic age, and tectonically overlapped by Paleozoic and Mesozoic juvenile crust in the central sector and its corresponding fore-arc region. It is also concluded in this work, in agreement with recent seismological high resolution studies, that the apparent differences existing between geophysical modeling and the P-T conditions required to generate the primary andesitic, dacitic and adakitic magmas that characterize the TMVB in the study area, may be resolved if the angle of the slab that extends northward and beyond the flat segment is increased substantially, thus creating optimal thermal and rheological conditions in a mantle wedge under the volcanic front much thicker than currently accepted. These conditions would increase the temperature of the entire subduction system to values that would permit the generation of such primary magmas by partial melting of the basaltic part of the subducting slab, the mantle wedge, and the mafic lower crust.